Transcriptome analysis in hepatopancreases reveals the response of domesticated common carp to a high-temperature environment in the agricultural heritage rice–fish system - Cheng, Xiangbing; Li, Fangcheng; Kumilamba, Gilbert; Liao, Jiayi; Cao, Jiangwei; Sun, Jiamin; Liu, Qigen (Frontiers in Physiology, 2023)
Qingtian paddy field carp (PF-carp) is a local carp cultivated in the paddy field of Qingtian, Zhejiang. This rice–fish co-culture system has been recognized as one of the Globally Important Agriculture Heritage Systems (GIAHS). PF-carp has been acclimatized to the high-temperature environment of shallow paddy fields after several centuries of domestication. To reveal the physiological and molecular regulatory mechanisms of PF-carp, we chose to use 28°C as the control group and 34°C as the treatment group. We measured biochemical parameters in their serum and hepatopancreases and also performed transcriptome sequencing analysis. Compared with the control group, the serum levels of malondialdehyde (MDA), glucose (GLU), glutathione peroxidase (GSH-Px), catalase (CAT), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) show no significant change. In addition, superoxide dismutase (SOD), GSH-Px, and CAT also show no significant change in hepatopancreases. We identified 1,253 differentially expressed genes (DEGs), and their pathway analysis revealed that heat stress affected AMPK signaling pathway, protein export, and other biological processes. It is worth noting that protein processing in the endoplasmic reticulum (ER) was the most significantly enriched pathway identified by the Kyoto Encyclopedia of Genes and Genomes (KEGG) and gene set enrichment analysis (GSEA). Significantly higher levels of HSP40, HSP70, HSP90, and other ubiquitin ligase-related genes were upregulated. In summary, heat stress did not lead to tissue damage, inflammation, oxidative stress, and ER stress in the hepatopancreases of PF-carp. This study provides valuable insights into the adaptation mechanism of this species to the high-temperature environment of paddy fields.